The Relationships between External Integration and Plant Improvement and Innovation Capabilities: The Moderation Effect of Product Clockspeed. Issue 3 (24th July 2013) - Peng, David X.; Verghese, Anto; Shah, Rachna; Schroeder, Roger G.
Abstract : Product clockspeed as represented by the rate of product changes has important implications for supply chain design. The literature suggests that external integration with customers and suppliers is associated with increased improvement and innovation capabilities of the focal firm. However, the way product clockspeed affects these relationships has seldom been subjected to empirical investigation. This study investigates whether product clockspeed moderates the relationship between external integration and improvement and innovation capabilities of manufacturing plants. Analysis of survey data collected from 238 manufacturing plants indicates a positive moderation effect of product clockspeed on the relationship between customer integration and plant improvement and innovation capabilities. However, product clockspeed does not have a significant moderation effect on the relationship between supplier integration and either of the two plant capabilities. This study provides theoretical and managerial insights into aligning external integration with plant capabilities under the contingency of product clockspeed.